Pengaruh Strategi Perusahaan, Transparansi, Kinerja ESG Terhadap Penghindaran Pajak Pada Perusahaan Konsumen Non-Cyclicals Sub Sektor Makanan dan Minuman Tahun 2020-2023 - Reza Fathurrahman; R. Rosiyana Dewi (EKOMA : Jurnal Ekonomi, Manajemen, Akuntansi, 2024)
This research aims to determine the influenceof Corporate Strategy, Transparency, and ESG Performance on Tax Avoidance within the ConsumerNon-Cyclical Companies operating in the Food andBeverage Sub Sector listed on the Indonesia StockExchange between 2020 and 2023. The data utilizedcomprises secondary data extracted from companyannual reports and sustainability reports accessiblethrough www.idx.co.id or individual company websites. Employing a purposive sampling approach withspecific criteria, a total of 196 data samples were obtained. The data analysis methodology includesdescriptive tests and panel data regression testsconducted using Eviews 12 software. The findings reveal that (1) Corporate Strategyexhibits no discernible influence on Tax Avoidance, (2) Transparency demonstrates a favorable impact on TaxAvoidance, and (3) ESG Performance does not exhibita significant effect on Tax Avoidance.